Renewable energy integration practical management of variability, uncertainty and flexibility in power grids - Jones, Lawrence E. (Academic Press, 2014)
Renewable Energy Integration is a ground-breaking new resource, the first to offer a distilled examination of the intricacies of integrating renewables into the power grid and electricity markets. It offers informed perspectives from internationally renowned experts on the challenges to be met, and solutions based on demonstrated best practices developed by operators around the world. The book's focus on practical implementation of strategies provides real-world context for theoretical underpinnings and the development of supporting policy frameworks.
Includes bibliographical references at the end of each chapters and index. - Print version record
Keywords: Renewable energy sources; Smart power grids; Electric power distribution; Renewable Energy; Énergies renouvelables; Réseaux électriques intelligents; BUSINESS & ECONOMICS; Real Estate; General